Implikasi Hukum Terhadap Peningkatan Sampah Ruang Angkasa Akibat Aktivitas Komersialisasi Ruang Angkasa - Muthia, Nuriyah Fara; Sumardi, Juajir; Maskun, Maskun (Al-Mizan (e-Journal), 2023)
This research aims to analyze the legal implications of the increase in space debris generated through space commercialization activities. This research uses a normative legal method using a qualitative approach to determine the application of law in commercial activities carried out in space. The results of this study, namely: (1) the increase in space junk cases caused by commercial activities in space is increasing until 2022 due to various satellites being launched and causing junk to scatter freely in space. The rules of the Outer Space Treaty 1967 are still unable to guarantee legal certainty so that all parties carrying out commercial activities in space obey them; (2) the calculation of damage caused by commercial activities in space will result in liability that has been regulated in the Space Liability Convention 1972 that there are two legal principles governing the responsibility for compensation carried out by all parties in space, both state and private parties.